HISTORY OF THE ORGANIZATION AND DEVELOPMENT OF PROSECUTOR'S OFFICES IN THE REPUBLIC OF UZBEKISTAN - Dilshod Pulatovich, Komolov (PT. Antis International Publisher, 2025)
Objective: This study examines the establishment and development of prosecutor's offices in the Republic of Uzbekistan from 1991 to 2000, focusing on the transition to independence and its impact on the legal system. Method: Utilizing historical sources and a comparative analysis of legal documents, this research investigates the structural and functional changes in the prosecutor's offices during this period. Results: Key developments include the separation of prosecutors from political parties, the advancement of theoretical and legal frameworks for the institution, personnel management reforms, and efforts to ensure uniform implementation of laws across the republic. Novelty: This work highlights the pivotal role of prosecutor's offices in shaping the legal foundations of independent Uzbekistan and offers a unique perspective on their evolution during a transformative decade.